Artificial intelligence in allergy practice: Digital transformation and the future of clinical care - Sandra Nora González-Díaz, MD, PhD; Mário Morais-Almeida, MD; Ignacio J. Ansotegui, MD, PhD; Carlos Macouzet-Sánchez, MD, PhD; Yeyetsy G. Ordóñez-Azuara, MD, PhD; José Camarena-Galván, MD; Jesús Marcelo Alanís-Alvarez, MD (World Allergy Organization Journal, 2025)
Bioethics involves the analysis of human behavior in the life and health sciences, grounded in moral values and ethical principles. Its integration into the education and training of healthcare professionals is essential for addressing complex medical dilemmas, while also fostering behaviors that strengthen the doctor-patient relationship. The rapid advancement of technology, particularly artificial intelligence (AI), is transforming medical specialties and reshaping patient care. In the field of allergy and immunology, AI offers promising applications such as enhanced patient education, symptom tracking, personalized treatment planning, and improved clinical decision-making. However, its implementation raises significant ethical concerns. There is a risk of diminishing clinical reasoning skills due to excessive reliance on AI, as well as challenges related to data privacy, informed consent, and algorithmic transparency. These issues pose new bioethical dilemmas regarding patient autonomy and the humanization of care. This review explores the integration of AI in allergy practice, emphasizing its ethical implications and its potential impact on the doctor-patient relationship. Balancing technological innovation with core bioethical principles—non-maleficence, beneficence, autonomy, and justice—is critical for advancing patient-centered care in a digital era.